Product Quality Analysis of Purchase Decisions with Consumer Trust in Honey Products Complex Bina Marga Wamena - Wahyuni Nurindah Sulistiowati; Syarifah; Fitri (LPPM UNAIM, 2021)
The aims of this study are: (1) To determine the effect of product quality on consumer confidence. (2) To determine the influence of consumers on purchasing decisions. (3) To determine the effect of the product on purchasing decisions. (4) To determine the effect of product quality on purchasing decisions through consumer trust. The research used is associative research, associative research is research that aims to determine the relationship between two or more variables. The approach used in data collection is the survey method, because the study was conducted on a large population and the data studied were data from samples taken from that population. The quality of a product has a positive and significant influence on consumer confidence. So the better the quality of a product offered to consumers, the higher consumer confidence.